Effectiveness of Game-Based Learning on Anxiety and Postoperative Self-Efficacy among Children Undergoing Surgery - Sofia, M.; Aranha, Priya Reshma (Journal of Health and Allied Sciences NU, 2022)
Background Play is an integral part of a child's life that could be effectively implemented for hospitalized children as well. It plays an important role in alleviating the psychological burden and enhancing self-efficacy of children undergoing surgery. Children benefit from play or games because they enjoy learning through them. The present study aims to assess the effectiveness of game-based learning on anxiety and postoperative self-efficacy among children undergoing surgery.Materials and Methods Using nonprobability purposive sampling technique, 80 school-age children undergoing surgery were selected. Children in the interventional group received game-based learning, whereas those in the control group received routine care. A numeric 0 to 10 state anxiety scale and a self-efficacy scale were used for assessing anxiety and postoperative self-efficacy of children. The obtained data was analyzed using descriptive and inferential statistics.Results Mann–Whitney U test showed significant difference (p < 0.05) between the mean pre- and posttests scores of anxiety in intervention group. Comparison of posttests anxiety scores between the groups also showed a statistical significance (p < 0.05). When compared self-efficacy scores within intervention and control groups, Wilcoxon signed-rank test value was significant (p < 0.05). Whereas between groups comparison the Mann–Whitney U test value was significant (p < 0.05) at 24 and 48 hours after surgery.Conclusion The study concluded that game-based learning is effective in maintaining adequate postoperative self-efficacy and reducing the anxiety among the children undergoing surgery.
Keywords: anxiety; children; game-based learning; postoperative self-efficacy